2015
DOI: 10.5152/jtgga.2015.15199
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of a real time optoelectronic device (TruScreen™) in detecting cervical intraepithelial pathologies: a prospective observational study

Abstract: Objective:To assess the effect of TruScreen™ (an objective optoelectronic cervical screening device) in improving the sensitivity of cervical screening programs either alone or in combination with Papanicolaou (PAP) smear or human papilloma virus (HPV) DNA screening. Material and Methods:Our study was performed in 285 patients with abnormal Pap test results. TruScreen™ and HPV screening methods were performed in all participants. Consistency and differences between the tests were compared with cervical biopsy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 13 publications
1
8
0
Order By: Relevance
“…demonstrated a 67.4% sensitivity for TruScreen™ and an 87.9% for conventional cytology in detections with a histological confirmation of CINs. [ 17 ] In 2014, the use of TruScreen™ as the screening procedure for detecting CC resulted in an 86.1% sensitivity and 35% specificity, demonstrating a greater sensitivity than the gold standard, which is the PAP, with instantaneous results and without the need for interpretation by cytopathology, which has the additional disadvantage of being operator-dependent. [ 18 ]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…demonstrated a 67.4% sensitivity for TruScreen™ and an 87.9% for conventional cytology in detections with a histological confirmation of CINs. [ 17 ] In 2014, the use of TruScreen™ as the screening procedure for detecting CC resulted in an 86.1% sensitivity and 35% specificity, demonstrating a greater sensitivity than the gold standard, which is the PAP, with instantaneous results and without the need for interpretation by cytopathology, which has the additional disadvantage of being operator-dependent. [ 18 ]…”
Section: Discussionmentioning
confidence: 99%
“…This is, to our knowledge, the first study conducted in Mexico and Latin America in which we can observe that for the detection of high-grade intraepithelial lesions, TruScreen™ demonstrated low sensitivity and high specificity compared with conventional cytology, with a high NPV. The impact of this study lies in the possible diagnostic usefulness of the TruScreen™ in not having to wait for the result of the PAP and in the fact that the results can be similar to those obtained by conventional cytology, in which the sensitivity can be similarly low, reaching 51.5%, as shown in a study performed in the U.S. with more than 47,000 patients submitted to a conventional cytology,[ 17 ] and the advantages of diminishing the need of a pathological report and establishing a protocol of treatment from the first clinical assessment prior to an abnormal result for the opto-electronic device. The greatest impact of the latter would be in primary care-level services, where a high percentage of patients who have a screening test, such as conventional cytology, do not return for the results or the results take a long time to be delivered.…”
Section: Onclusionsmentioning
confidence: 93%
“…TruScreen (TS) is a non-invasive diagnostic method for CIN with immediate and automatically generated results [13]. Briefly, it detects and analyzes cervical tissues through optoelectronic signals emitted from the tip of the device.…”
Section: Introductionmentioning
confidence: 99%
“…However, at present, most of the studies on cervical cancer screening by TS have been based on small sample clinical patients, and the evaluation of the screening effect of TS has shown wide differences in different studies. Some studies showed that the effect of TS is consistent with that of cytology, but some studies show that its screening effect is not as good as that of cytology [10][11][12]. So in the real world, is there any difference in the detection rate of cervical lesion between TS and human papillomavirus (HPV) test and Liquid-based cytology (LBC) test which currently used in the project area of NCCSPRA?…”
Section: Introductionmentioning
confidence: 99%